A policy taxonomy for agricultural transformation - Balino, Sofia; Laborde Debucquet, David; Murphy, Sophia; Parent, Marie; Smaller, Carin; Traoré, Fousseini (International Institute for Sustainable Development, 2019)
What are the policies that drive agricultural transformation? And how can they be classified to support decision making? These are the key questions that drove the development of a policy taxonomy for agricultural transformation, with a focus on those that affect prices in agricultural markets. This taxonomy is derived from the original framework of four broad categories and nine sub-categories used in Transforming Agriculture in Africa and Asia: What Are the Policy Priorities? and an assessment of over 250 articles. This taxonomy moves beyond the category approach. Instead, it examines the underlying target of the policy, i.e., whether the policy is primarily targeting agricultural markets, the rural economy, the macroeconomy, or the institutions that shape socioeconomic relationships. This shift in approach was designed to help decision-makers prioritize options.